Ye that are men now serve him : radical holiness theology and gender in the South - Chapell, Colin B., 1982- (Tuscaloosa : University of Alabama Press, 2016)
Modernity remade much of the world in the late nineteenth and early twentieth centuries and was nowhere more transformational than in the American South. In the wake of the Civil War, the region not only formed new legal, financial, and social structures, but citizens of the South also faced disorienting uncertainty about personal identity and even gender itself. Ye That Are Men Now Serve Him traces the changes in southern gender roles during the New South period of 1877-1915 and demonstrates that religion is the key to perceiving how constructions of gender changed. The Civil War cleaved southerners from the culture they had developed organically during antebellum decades, raising questions that went to the very heart of selfhood: What does it mean to be a man? How does a good woman behave? Unmoored from traditional anchors of gender, family, and race, southerners sought guidance from familiar sources: scripture and their churches. In Ye That Are Men Now Serve Him, Colin Chapell traces how concepts of gender evolved within the majority Baptist and Methodist denominations as compared to the more fluid and innovative Holiness movement. Grounded in expansive research into the archives of the Southern Baptist Convention; Methodist Episcopal Church, South; and the Holiness movement, Chapell's writing is also enlivened by a rich trove of primary sources: diaries, sermons, personal correspondence, published works, and unpublished memoirs. Chapell artfully contrasts the majority Baptist and Methodist view of gender with the relatively radical approaches of the emerging Holiness movement, thereby bringing into focus how subtle differences in belief gave rise to significantly different ideas of gender roles. Scholars have explored class, race, and politics as factors that contributed to contemporary southern identity, and Chapell restores theology to its intuitive place at the center of southern identity. Probing and illuminating, Ye That Are Men Now Serve Him offers much of interest to scholars and readers of the South, southern history, and religion. --
Establishing the standards of evangelical identity -- Baptists and Methodists in the new South -- Faithful Baptist families and women -- Masterful manhood in the Southern Baptist Convention -- The manly soldiers of Methodism -- Methodist women as home missionaries -- Radical theology and radical identity -- Defining holiness -- Consecrated regardless of sex -- Perfect masculine love.
Includes bibliographical references and index.
Print version record.
Keywords: Southern States -- Church history -- 19th century; Southern States -- Church history -- 20th century; Sex role -- Religious aspects -- Christianity -- History -- 19th century; Sex role -- Religious aspects -- Christianity -- History -- 20th century; Holiness movement -- Southern States; Baptists -- Southern States -- History; Methodist Church -- Southern States -- History; Evangelicalism -- United States; Baptists; Evangelicalism; Holiness movement; Methodist Church; Sex role -- Religious aspects -- Christianity; Southern States; United States; RELIGION / Christianity / History; 1800-1999; Church history; History; Electronic books